The Africa Platform and its awareness-raising activities. Panel discussion on the future of Rwanda (13 May 2015) - Verdoolaege, Annelies (Afrika Focus, 2015)
The reactions to this event were generally very positive; a great many interesting issues were touched upon and the atmosphere of the discussion allowed sufficient room for various points of view and an optimistic view on the future of Rwanda to be expressed. This was an excellent example of an event in which academic Africa expertise is made available to inform a broad public, in conjunction with an artistic performance. Also the input provided by the Rwandan diaspora was greatly valued. In the future, this is definitely the way in which the African Platform of Ghent University Association wishes to present itself to the academic community and beyond.